CULTURALITY ON YOUTUBE FEATURES:A CASE ON MEDIA LINGUISTIC APPROACH - Tatan Tawami; Retno Purwani Sari (Majalah Ilmiah UNIKOM, 2025)
Language evolves as technology advances with novel applications, such as social media. Their interaction raises a new issue in the evolution of language science: culture-linguistics (culturality). The study seeks to uncover the cultural meanings of language forms (signs), mainly social media, YouTube, and their social purposes. The qualitative method was used in this study, and a media linguistics approach was used to describe the analysis systematically. According to this research, the features in the mentioned social media are made up of visual and verbal signs arranged to serve their social purposes of self-presentation, integration, or differentiation. In conclusion, every YouTube channel has its unique way of presenting itself to the audience depending on their preferred so-called ideology. The findings give specific feedback to social media users about the specialized norms/values implicit in the features, making them aware of the seamless use of social media, YouTube.